Optimizing Fish Production: The Influence of Digital Technologies on Sustainability and Well-being of Indonesian Artisanal Fishermen - Barlian, Erland (Universitas Bunda Mulia, 2025)
This study examines the impact of early Industry 4.0 digital technologies on the sustainability and entrepreneurial well-being of Indonesian small-scale fishermen. Despite abundant marine resources, their sustainable livelihoods are challenged by the commercial fishing industry’s unbalanced performance. Employing quantitative methods and surveys in western Indonesia, the research reveals a significant link between artisanal fishermen as entrepreneurs and the sea as a natural resource provider, crucially mediated by digital transformation. To achieve both short-term and long-term sustainability, harnessing the potential of digital technology for responsible sea exploitation is essential. Findings indicate that digital transformation significantly enhances the relationship between fishermen and the maritime ecology. By embracing digital solutions, artisanal fishermen can optimize resource utilization, improve operational efficiency, and enhance their overall well-being, ensuring the long-term viability of small-scale fisheries.